2008
DOI: 10.1128/mcb.00524-07
|View full text |Cite
|
Sign up to set email alerts
|

Rad51-Independent Interchromosomal Double-Strand Break Repair by Gene Conversion Requires Rad52 but Not Rad55, Rad57, or Dmc1

Abstract: Homologous recombination (HR) is critical for DNA double-strand break (DSB) repair and genome stabilization. In yeast, HR is catalyzed by the Rad51 strand transferase and its "mediators," including the Rad52 single-strand DNA-annealing protein, two Rad51 paralogs (Rad55 and Rad57), and Rad54. A Rad51 homolog, Dmc1, is important for meiotic HR. In wild-type cells, most DSB repair results in gene conversion, a conservative HR outcome. Because Rad51 plays a central role in the homology search and strand invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…The differences between the ILT and the ALT-like pathways, both amplifying the TG 1-3 repeats (type II), were an absence of a requirement for Rad52, Rad59, and functional RPA for the ILT pathway, in contrast to the type II-ALT pathway, which requires all three proteins. Gene conversion, which normally requires both Rad51 and Rad52, can be possible in the absence of Rad51 for ectopic events but, surprisingly, also for interchromosomal conversion (61,62,67). Allelic conversion is also possible in the absence of Rad52 but not in the absence of both Rad51 and Rad52 (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between the ILT and the ALT-like pathways, both amplifying the TG 1-3 repeats (type II), were an absence of a requirement for Rad52, Rad59, and functional RPA for the ILT pathway, in contrast to the type II-ALT pathway, which requires all three proteins. Gene conversion, which normally requires both Rad51 and Rad52, can be possible in the absence of Rad51 for ectopic events but, surprisingly, also for interchromosomal conversion (61,62,67). Allelic conversion is also possible in the absence of Rad52 but not in the absence of both Rad51 and Rad52 (62).…”
Section: Discussionmentioning
confidence: 99%
“…Gene conversion, which normally requires both Rad51 and Rad52, can be possible in the absence of Rad51 for ectopic events but, surprisingly, also for interchromosomal conversion (61,62,67). Allelic conversion is also possible in the absence of Rad52 but not in the absence of both Rad51 and Rad52 (62). It is assumed that each of these proteins can perform part of the other one's functions in its absence.…”
Section: Discussionmentioning
confidence: 99%
“…studies on HR revealed several recombination pathways that do not require Rad51; they include SSA and BIR, although a majority of BIR is dependent on Rad51 (43,46,(75)(76)(77). In addition, a subset of sister chromatid recombination (SCR) events, which is facilitated by the RSC chromatin-remodeling complex, also can occur independently of Rad51 (78,79).…”
Section: Suppression Of Dna2-k1080e By Rad52 Depends On Several Factomentioning
confidence: 99%
“…The human Rad51B-Rad51C-Rad51D-Xrcc2 complex preferentially binds to branched DNA substrates, including a synthetic Holliday junction substrate, over other DNA substrates (Yokoyama et al 2004). XRCC3-and RAD51C-defective cell lines exhibit longerthan-normal gene conversion tract lengths, which could result from defects in the resolution of recombination intermediates or be due to a different mode of recombination by the Rad51-independent pathway (Brenneman et al 2002;Nagaraju et al 2006;Pohl and Nickoloff 2008). Extracts made from XRCC3-or RAD51C-defective Chinese hamster ovary cells show reduced levels of Holliday junction resolvase activity (Liu et al 2004).…”
Section: H Omologous Recombination Is Required Formentioning
confidence: 99%